Institutional Identity Construction on Instagram: Faculties of Sport Sciences - Tuğba Ertuğral; Necati Gürses; Kıvanç Semiz (IUC University Press, 2024)
The aim of this study is to examine the institutional identity construction of the faculties of sports sciences on Instagram. The study group for the research consists of individuals who manage the Instagram accounts of sports science faculties of eight universities operating in Turkey. In this study, the case study design, which is one of the qualitative research types, was used. Since there is more than one situation that can be perceived as a whole on its own, the holistic multiple-case design, which is one of the types of case study, was chosen. Before analyzing the data, a research triangulation was provided by an expert interviewer to ensure credibility. Data were collected through structured interviews with eight participants. It was recorded by interviewing the people who manage the Instagram page over the internet. The analysis of the data obtained from the interviews was carried out by making thematic content analyses with the MaxQDA program. According to content analysis results, the corporate identity construction process of the sports science faculties of eight state universities operating in Turkey via Instagram. Postmodern communication was evaluated in four main themes such as online instant interaction, online presentation of the institution, and the role of social media leader, and each theme was discussed within itself.